The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1523/jneurosci.0509-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

SPARC from Olfactory Ensheathing Cells Stimulates Schwann Cells to Promote Neurite Outgrowth and Enhances Spinal Cord Repair

Abstract: Olfactory ensheathing cells (OECs) transplanted into the lesioned CNS can stimulate reportedly different degrees of regeneration, remyelination, and functional recovery, but little is known about the mechanisms OECs may use to stimulate endogenous repair. Here, we used a functional proteomic approach, isotope-coded affinity tagging and mass spectrometry, to identify active components of the OEC secreteome that differentially stimulate outgrowth. SPARC (secreted protein acidic rich in cysteine) (osteonectin) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
101
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 119 publications
(103 citation statements)
references
References 79 publications
(110 reference statements)
2
101
0
Order By: Relevance
“…SPARC promotes axon outgrowth indirectly, by enhancing the ability of Schwann cells to support neurite outgrowth (Bampton et al, 2005;Au et al, 2007). When SPARC null OECs are transplanted into the injured rat spinal cord, the outgrowth of specific subsets of sensory and supraspinal axons is reduced, and the immune response is altered (Au et al, 2007). Furthermore, in the absence of OECderived SPARC, we found that SPARC is present in endogenous glia surrounding the lesion site (Au et al, 2007), which further supports a potential role for SPARC in CNS repair.…”
Section: Introductionsupporting
confidence: 66%
See 4 more Smart Citations
“…SPARC promotes axon outgrowth indirectly, by enhancing the ability of Schwann cells to support neurite outgrowth (Bampton et al, 2005;Au et al, 2007). When SPARC null OECs are transplanted into the injured rat spinal cord, the outgrowth of specific subsets of sensory and supraspinal axons is reduced, and the immune response is altered (Au et al, 2007). Furthermore, in the absence of OECderived SPARC, we found that SPARC is present in endogenous glia surrounding the lesion site (Au et al, 2007), which further supports a potential role for SPARC in CNS repair.…”
Section: Introductionsupporting
confidence: 66%
“…This suggests that SPARC may be involved in regulating plasticity and repair in the CNS. In support of this, we have shown that SPARC is a major component of the neurite outgrowth-promoting activity of OEC-conditioned medium in a dorsal root ganglion assay (Au et al, 2007). SPARC promotes axon outgrowth indirectly, by enhancing the ability of Schwann cells to support neurite outgrowth (Bampton et al, 2005;Au et al, 2007).…”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations